Fever in the Returned Pediatric Traveler - Nahed Abdel-Haq MD; Basim I. Asmar MD (SAGE Publishing, 2021)
Global mobility has been steadily increasing in recent years. The assessment of the febrile child returning from international travel is a diagnostic challenge. The COVID-19 pandemic has profoundly affected international travel and made evaluation and management of the sick returned traveler more challenging. Children visiting friends and relatives abroad remain at higher risk of infection compared to tourists. This review presents a guidance on the initial assessment of a traveling febrile child including interpretation of medical history, physical examination, and laboratory findings. Important clues to etiology include exposure to different infectious agents, incubation periods of pathogens, and prophylaxis regimens and vaccines received. Early identification of potentially life-threatening and highly contagious infections is essential. In this article, we discuss the epidemiology, evaluation, and management of specific travel related infections such as malaria, typhoid fever, dengue fever, viral hemorrhagic fever, rickettsiosis, leptospirosis, schistosomiasis, gastrointestinal, and respiratory infections.